Pembelajaran Ilmu Pengetahuan Sosial sebagai Sarana Pembentukan Karakter Siswa Menghadapi Revolusi Industry 4.0 - Mulyadi, Gallih Arya; Firman, Firman; Rusdinal, Rusdinal (Syntax Idea, 2021)
This research was conducted at the Faculty of Teacher Training and Education (FKIP), Pancasila and Citizenship Education (PPKn) Study Program, Pattimura University. During the new normal period (Pandemic Covid-19), Pattimura University implemented an online learning process in all Faculties, at the Teaching and Education Faculty, especially the PPKn Study Program, online learning became a separate obstacle for PPKn Lecturers in providing learning information due to college students inactive and inadequate focus during the learning process. In an effort to ensure that the online learning process can continue to be carried out well, this research was conducted. This study aims to implement an effective online learning evaluation to determine the level of understanding of PPKn college students in receiving course material. In this research, the online learning evaluation system implemented includes: (a) learning journals as college students evaluation materials in reviewing the material presented, (b) case studies as a way of thinking of college students in expressing opinions related to issues that occur in society, (c) film review articles as a form of creativity, knowledge to hone college students writing skills, (d) teaching simulation as a method to develop college student teaching skills as prospective educators. The research method used is descriptive qualitative to describe the alternative solution to the problem of learning evaluation. The results showed that the implementation of online learning evaluation can make it easier for lecturers to assess the extent of the success of the implementation of online learning in the PPKn Study Program, especially during the Pandemic Covid-19.